Identificamos las ideas de un texto y expresamos nuestras opiniones - Ramos Ramos, Nelly Lilian (2019)
When the students do identify the texts they prefer, they can get a linguistic development at the expression and comprehension levels as well as they can develop both their oral competence and performance and their reading comprehension ability._x000D_ This t eaching proficiency piece o work entitled “Identifying the ideas of a text and expressing opinion” involves the learning session design, the theoretical support, the didactic support and the conclusions. It has been designed for the third grade primary school boys and girls of “Juan Pablo II” school in Trujillo city, year 2019._x000D_ The learning session reached the learning goal since the reading comprehension ability was developed by identifying the main ideas and expressing opinion regarding the text all of which led to a meaningful learning.